Gromov-Hausdorff stability for semilinear systems with large diffusion - Lee, Jihoon; Nguyen, Ngocthach; Pires, Leonardo (Topological Methods in Nonlinear Analysis, 2024)
This paper deals with the Gromov-Hausdorff stability for systems generated of reaction-diffusion equations whose diffusion coefficients are simultaneously large in a bounded smooth domains. The appropriated framework is presentedto establish the conjugation between the attractors by means of $ε$-isometries.